SUIT: The Pascal of User Interface Toolkit - Pausch, Randy; II, Nathaniel R. Young; DeLIne, Robert (UIST '91 Proceedings of the 4th annual ACM symposium on User interface software and technology, 1991)
User interface support software, such as UI toolkits, UIMSs, and interface builders, are currently too complex for undergraduates. Tools typically require a learning period of several weeks, which is impractical in a semester course. Most tools are also limited to a specific platform, usually either Macintosh, DOS, or UNIX/X. This is problematic for students who switch from DOS or Macintosh machines to UNIX machines as they move through the curriculum. The situation is similar to programming languages before the introduction of Pascal, which provided an easily ported, easily learned language for undergraduate instruction. SUIT (the Simple User Interface Toolkit), is a C subroutine library which provides an external control UIMS, an interactive layout editor, and a set of standard screen objects. SUIT applications run transparently across Macintosh, DOS, UNIX/X, and Silicon Graphics platforms. Through careful design and extensive user testing of the system and its documentation, the authors have been able to reduce learning time. They have formally measured that new users are productive with SUIT in less than three hours. SUIT currently has over one hundred students using it for undergraduate and graduate course work and for research projects.